2022
DOI: 10.1093/advances/nmab114
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prebiotics, Synbiotics, and Short-Chain Fatty Acids on Respiratory Tract Infections and Immune Function: A Systematic Review and Meta-Analysis

Abstract: Prebiotics, synbiotics and short-chain fatty acids (SCFA) have been shown to decrease systemic inflammation and play a protective role in chronic respiratory conditions. However, the effect on infection and immune function are unclear. The objective of this systematic review was to summarise the current evidence for prebiotic, synbiotic and SCFA supplementation on respiratory tract infections (RTIs) and immune function. Relevant English language articles up to May 2021 were identified via online databases: MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Concerning the preventive effects provided by probiotics, three systematic reviews and meta-analyses examined this issue. [53][54][55] The first study evaluated the impact of prebiotics, synbiotics, and short-chain fatty acids on RRIs with 58 trials. 53 This analysis concluded that oligosaccharide supplementation was effective in infants and children.…”
Section: Intergroup Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the preventive effects provided by probiotics, three systematic reviews and meta-analyses examined this issue. [53][54][55] The first study evaluated the impact of prebiotics, synbiotics, and short-chain fatty acids on RRIs with 58 trials. 53 This analysis concluded that oligosaccharide supplementation was effective in infants and children.…”
Section: Intergroup Analysismentioning
confidence: 99%
“…[53][54][55] The first study evaluated the impact of prebiotics, synbiotics, and short-chain fatty acids on RRIs with 58 trials. 53 This analysis concluded that oligosaccharide supplementation was effective in infants and children. The second study analyzed probiotic-fermented dairy products, selecting 22 randomized controlled trials.…”
Section: Intergroup Analysismentioning
confidence: 99%
“…Quality control is vital for the effectiveness of probiotic products; however, inconsistencies in manufacturing processes and storage conditions can affect product quality, leading to variations in clinical outcomes 196 . In terms of the above challenges, prebiotics have more advantages than probiotics, but they still need the assistance of probiotics to exert their functions 197 . Regulatory concerns arise due to the varying classification of probiotics, prebiotics, postbiotics as dietary supplements, food additives, or medicines among countries, leading to differing regulatory standards and approval processes 198 .…”
Section: Challenges Of Probiotics Prebiotics and Postbiotics As Medic...mentioning
confidence: 99%
“… 196 In terms of the above challenges, prebiotics have more advantages than probiotics, but they still need the assistance of probiotics to exert their functions. 197 Regulatory concerns arise due to the varying classification of probiotics, prebiotics, postbiotics as dietary supplements, food additives, or medicines among countries, leading to differing regulatory standards and approval processes. 198 The consumption of live bacteria in probiotics or certain types of prebiotics and postbiotics may conflict with some cultural or religious beliefs.…”
Section: Challenges Of Probiotics Prebiotics and Postbiotics As Medic...mentioning
confidence: 99%
“…This review concluded that supplementation with prebiotics-especially Oss-may play a role in reducing the incidence and duration of respiratory tract infections in infants and children. There is insufficient evidence of this protective effect for the adult population [50]. Rashidi et al concluded in 2021 that supplementation with prebiotics, probiotics, and synbiotics in infant formula (PRO-formula) plays a protective role against respiratory tract infections.…”
Section: Systematic Reviewsmentioning
confidence: 99%